Introducing Agile Methods in Undergraduate Curricula, a Systematic Mapping Study - Paéz, Nicolás (2019)
Agile approaches to Software Engineering are widely used nowadays in industry and have also reached academic environments, with universities all around the world including agile related content in their programs. There are no formal studies about the current situation of Agile Software Development in Argentinian Universities. A systematic mapping study was conducted to understand the state of agile in undergraduate curricula. Results show that Agile Software Development is part of the Information Technology and Computer Science Programs and that Scrum is the most popular agile method in that context. There is little information regarding the teaching strategy used but a learningby- doing approach is used in many cases.